2015
DOI: 10.1007/s00339-015-9341-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation acceleration of calcium hydroxide nanoparticles: induced by yeast fermentation

Abstract: 8Carbonation of Ca(OH)2 nanoparticles and consolidation of limestone are accelerated 9 by high humidity and a yeast fermentation system that supplies a saturated 10 atmosphere on CO2, H2O vapor and ethanol during 28 days. Nanoparticles were 11analyzed by X-ray diffraction and differential thermal analyses with thermogravimetry. 12Spectrophotometry, scanning electron microscopy analyses, hydric and mechanical 13tests were also performed in stones specimens. Samples exposed to the yeast 14 environment achieve 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…However, the addition of NaHCO 3 may induce the formation of salt efflorescence. Furthermore, other studies focused on creating a CO 2 -rich atmosphere in a yeast-sugar environment to accelerate the carbonation process and to increase the in-depth carbonation [26]. Recently, other studies suggested that the type of solvent could be critical for the nanolime effectiveness in highly porous substrates [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of NaHCO 3 may induce the formation of salt efflorescence. Furthermore, other studies focused on creating a CO 2 -rich atmosphere in a yeast-sugar environment to accelerate the carbonation process and to increase the in-depth carbonation [26]. Recently, other studies suggested that the type of solvent could be critical for the nanolime effectiveness in highly porous substrates [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Progress in the use of consolidating products based on calcium hydroxide nanoparticles for the consolidation of carbonate stone materials has been increasing in the last years. One of the main objectives has been to improve its properties to ensure the success of the process, including control of morphology and size of the nanoparticles (24), rate and the effect of carbonation in crystal growth (25), degree of crystallinity, penetration depth, concentration of solution (23), additives, catalysers (26) or solvents, and solubility (27).…”
Section: Consolidants Based On Ca(oh) 2 Nanoparticles Applied In Rockmentioning
confidence: 99%
“…The carbonation process of nanolime may be accelerated or even completed by the addition of a source of CO 2 : baking soda (NaHCO 3 ) or yeast–sugar solutions . Upon adding an external CO 2 source, that is, a solution of NaHCO 3 , a conversion factor of 95 % can be reached .…”
Section: Alkaline Earth Metal Hydroxide Np Dispersionsmentioning
confidence: 99%
“…In a high‐humidity environment and without the favorable effect of the addition of CO 2 , conversion of 95 % to the same mineral phases (aragonite and calcite) for the same number of days can be achieved. Samples exposed to lower humidity (laboratory room conditions) display much lower rates of carbonation of the initial portlandite NPs and yield 85 % portlandite and 15 % calcite in 28 days . In the three different environments (with and without yeast at high humidity and without yeast under ambient conditions), all limestone specimens consolidated with these NPs show an increase in their mechanical properties.…”
Section: Alkaline Earth Metal Hydroxide Np Dispersionsmentioning
confidence: 99%
See 1 more Smart Citation